When to use drugs to help sleep. Issue 11 (1st August 2008) - Gringras, P
Abstract : Paediatric sleep medicine is a relatively new but important and rapidly growing field. It is increasingly recognised that many "adult" sleep disorders begin in childhood where the consequences of missed diagnoses can be devastating. Adequate training of all health care professionals and careful eliciting of symptoms remains the first step in ensuring accurate and timely diagnoses. Although behavioural approaches play a huge role in paediatric sleep medicine, at times severe sleep disorders also require pharmacological treatments. However, the evidence base for these is weak, and currently treatments of conditions including insomnia, narcolepsy and restless legs syndrome in childhood still rely on hopeful extrapolation from adult data. A growth in randomised controlled trials over the last 5 years is encouraging; trial methodologies are also improving. International working groups and multicentre trials will increasingly be needed to evaluate the new technologies and pharmacological treatments that are emerging.